The expression patterns and correlations of claudin-6, methy-CpG binding protein 2, DNA methyltransferase 1, histone deacetylase 1, acetyl-histone H3 and acetyl-histone H4 and their clinicopathological significance in breast invasive ductal carcinomas - Xu Xiaoming; Jin Huiying; Liu Yafang; Liu Li; Wu Qiong; Guo Yaxiong; Yu Lina; Liu Zhijing; Zhang Ting; Zhang Xiaowei; Dong Xueyan; Quan Chengshi (BMC, 2012)
Abstract Background Claudin-6 is a candidate tumor suppressor gene in breast cancer, and has been shown to be regulated by DNA methylation and histone modification in breast cancer lines. However, the expression of claudin-6 in breast invasive ductal carcinomas and correlation with clinical behavior or expression of other markers is unclear. We considered that the expression pattern of claudin-6 might be related to the expression of DNA methylation associated proteins (methyl-CpG binding protein 2 (MeCP2) and DNA methyltransferase 1 (DNMT1)) and histone modification associated proteins (histone deacetylase 1 (HDAC1), acetyl-histone H3 (H3Ac) and acetyl- histone H4 (H4Ac)). Methods We have investigated the expression of claudin-6, MeCP2, HDAC1, H3Ac and H4Ac in 100 breast invasive ductal carcinoma tissues and 22 mammary gland fibroadenoma tissues using immunohistochemistry. Results Claudin-6 protein expression was reduced in breast invasive ductal carcinomas (P < 0.001). In contrast, expression of MeCP2 (P < 0.001), DNMT1 (P = 0.001), HDAC1 (P < 0.001) and H3Ac (P = 0.004) expressions was increased. Claudin-6 expression was inversely correlated with lymph node metastasis (P = 0.021). Increased expression of HDAC1 was correlated with histological grade (P < 0.001), age (P = 0.004), clinical stage (P = 0.007) and lymph node metastasis (P = 0.001). H3Ac expression was associated with tumor size (P = 0.044) and clinical stage of cancers (P = 0.034). MeCP2, DNMT1 and H4Ac expression levels did not correlate with any of the tested clinicopathological parameters (P > 0.05). We identified a positive correlation between MeCP2 protein expression and H3Ac and H4Ac protein expression. Conclusions Our results show that claudin-6 protein is significantly down-regulated in breast invasive ductal carcinomas and is an important correlate with lymphatic metastasis, but claudin-6 down-regulation was not correlated with upregulation of the methylation associated proteins (MeCP2, DNMT1) or histone modification associated proteins (HDAC1, H3Ac, H4Ac). Interestingly, the expression of MeCP2 was positively correlated with the expression of H3Ac and H3Ac protein expression was positively correlated with the expression of H4Ac in breast invasive ductal carcinoma Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/4549669866581452